Lessons Learned from the Last Moments Captured of Traditional Small-Scale Land Use in a European Fen Meadow - Előd Búzás; Judit Bódis (Land)
Most of Europe’s semi-natural grasslands have been maintained by land use for thousands of years. Consequently, as a side effect of this type of land use, high grassland biodiversity was able to develop in those areas. Today, due to changes in land use, only fragments of the native grasslands and their biodiversity, especially in wetlands, remain. We conducted a study on changes in land use and the conservation context of a species-rich Hungarian fen meadow over 250 years. In addition to the main changes, we focused on sustainable grassland management. For our research, we built a geospatial database in which we attached great importance to georeferenced aerial photographs taken decades ago. To better understand what we can see in aerial photographs, we studied archived newspaper articles and conducted interviews. An aerial photograph taken in 1963 served as an exceptional illustration and data source for the key factors of sustainability and biodiversity. Our case study illustrates most of the major global problems affecting the European fen meadow (drainage, agricultural intensification, expansion of infrastructure networks, abandonment of farming). Based on our research, mosaic, adaptive, small-scale landscape use is necessary for the long-term sustainability of European wet grasslands and their special wildlife.